A rare case report: successful outcome of a patient at near term pregnancy with maternal chronic obstructive hydrocephalus due to tubercular meningitis - Mahesh, Sowmya; Srivastava, Himshweta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
The incidence of tubercular meningitis leading to obstructive hydrocephalus is extremely rare accounting for 1% cases and is even rarer during pregnancy. A 20-year-old 2nd Gravida presented at 32 weeks gestation with complaints of intermittent headache, decreased vision since 3 months and irrelevant talks and agitated behavior since 1 day. On examination patient had stable vital signs but constant irritable behavior. Obstetric examination revealed a pregnancy corresponding to 32 weeks with a live fetus. Patient had a past history of Anti-tubercular therapy taken 2 years back for tubercular meningitis. Neurological examination revealed a GCS of 12/15 and Ophthalmologic examination revealed patient to be having only Perception of Light with optic atrophy on fundoscopy. NCCT head revealed moderate dilatation of bilateral ventricles and 3rd ventricle without any periventricular ooze suggestive of Chronic Obstructive Hydrocephalus. Supportive therapy was instituted with Dexamethasone and Mannitol infusion after Neurosurgical consultation along with antenatal care. Decision for termination of pregnancy was taken at 35 weeks by an elective caesarean section with simultaneous ventriculo-peritoneal shunt insertion by neurosurgical team under general anesthesia. A live male baby of 2.25 kg was delivered. Patient with baby was discharged on 10th post-operative day. Obstructive hydrocephalous developing post tubercular meningitis in pregnancy is a rare event. Caesarean section was done along with shunt surgery in our case. Very few cases have been reported in the medical literature so far.